Implication of the White Group in Perspective of the Democracy Development in Indonesia - Soebagio, H. (UI Scholars Hub, 2008)
Politic participation in democratic State is an indicator of valid implementation of highest State power exercise by people (people sovereignty), that is imbodied by their involvement in democracy event (general elections). The increasingly higher level of political participation indicates that people follow, understand, and engange in national activities. Reversely, a low level of political participation generally indicates that people place less appreciation or interest in national affairs or activities. The low level of peoples’s political participation is reflected in golput (golongan putih-white group or non-voting) attitude. In democratic perspective, golput attitude will of course has implication on development of democracy quality, so it needs democratization in facing democratic event of 2009.